Perceptions of Educational Managers about the Effectiveness of Selected Training Programmes: A Case Study in the Ministry of Education, Oman - Alaraimi, Aisha; Othman, Azam (IIUM Journal of Educational Studies, 2015)
The present study evaluated the characteristics and effectiveness of selected training programmes for educational managers at the Ministry of Education in the Sultanate of Oman. Nine participants were selected for in-depth interview using the snowball sampling technique. Thematic analysis of the verbatim data collected from interviews with respondents yielded six major themes. These are: the objectives of the training program and how those objectives are formulated; trainee selection, prior knowledge, and general characteristics; contents or subject matter of training; training setting, trainer qualities, and the methods, tools and techniques used; outcomes of training in terms of changed characteristics and improved performance; and finally, mechanisms in place for evaluation and general impressions of the effectiveness of training programmes. The findings showed that, in general, participants were positive about the intensive efforts the ministry is undertaking for disseminating a training culture among staff members. Most of the respondents were satisfied with the training approaches and methods adopted by the trainers. Furthermore, the findings revealed that trainees were satisfied with the suitability and adequateness of training techniques, training aids and resources. These results will be useful for future researchers intending to conduct impact assessment of the effectiveness of training programs in Oman. Abstrak: Kajian ini menilai ciri-ciri dan keberkesanan program latihan bagi pengurus pendidikan di Kementerian Pelajaran dalam kerajaan Kesultanan Oman. Sembilan (9) orang peserta telah dipilih khusus untuk temubual dengan menggunakan teknik persampelan bola salji. Dapatan kajian menunjukkan bahawa bahagian pembangunan sumber manusia (PTM) sedang melaksanakan usaha-usaha intensif dalam pengedaran budaya latihan di kalangan kakitangan KPM, 78% daripada mereka yang ditemubual tidak berpuas hati dengan pendekatan latihan dan kaedah-kaedah yang diguna pakai oleh jurulatih. Selain itu, dapatan kajian mendedahkan bahawa pelatih berpuas hati dengan kesesuaian dan kecukupan teknik-teknik latihan, bantuan latihan dan latihan sumber. Antara penemuan kajian yang boleh menyumbang kepada ilmu pengetahuan adalah penghasilan kerangka yang berguna bagi mengukur ciri-ciri dan keberkesanan latihan peringkat program dan kecekapan Pengurus pendidikan. Adalah disyorkan supaya Kementerian Pelajaran harus menaik taraf dan memperluaskan infrastruktur latihan sedia ada di Kementerian berkenaan dan juga mempertimbangkan bakal pelatih program latihan. Kajian ini dijangka dapat menarik minat orang-orang berkepentingan yang berurusan dengan latihan dalam bidang pendidikan, bukan sahaja di Kementerian Pelajaran tetapi di institusi-institusi lain di mana latihan Pengurus adalah penting.